Facile Access to Ring-Fused Aminals via Direct α-Amination of Secondary Amines with o-Aminobenzaldehydes: Synthesis of Vasicine, Deoxyvasicine, Deoxyvasicinone, Mackinazolinone, and Ruteacarpine - Richers, Matthew T.; Deb, Indubhusan; Platonova, Alena Yu.; Zhang, Chen; Seidel, Daniel (Synthesis, 2013)
Secondary amines undergo redox-neutral reactions with aminobenzaldehydes under conventional and microwave heating to furnish polycyclic aminals via amine α-amination/N-alkylation. This unique α-functionalization reaction proceeds without the involvement of transition metals or other additives. The resulting aminal products are precursors for various quinazolinone alkaloids and their analogues.
Keywords: C–H bond functionalization; redox isomerization; aminals; quinazolinone alkaloids; Friedländer condensation